Integrating Maqashid Sharia in Climate Change Management and Economic Welfare of Coffee Farmers - Alfarisi, Azida; Syahputra, Hendra (JURNAL HURRIAH: Jurnal Evaluasi Pendidikan dan Penelitian, 2025)
Climate change has become a global phenomenon that creates ecological and economic pressures, and substantially impacts coffee's stability and productivity in Central Aceh. This study aims to examine the influence of climate change on the economic welfare level of coffee farmers in Central Aceh District. This research uses a qualitative method with a phenomenological approach. Data were collected through in-depth interviews with 30 coffee farmers in Central Aceh District, spread across Bebesen, Pegasing, and Silih Nara sub-districts. The results showed that climate change, characterised by temperature fluctuations, rainfall uncertainty, and changes in air humidity, had an impact on decreasing coffee productivity, increasing production costs, and decreasing farmers' income. In terms of maqashid sharia, this condition hinders the fulfilment of the five aspects of hifz ad-din (safeguarding religion), hifz an-nafs (safeguarding the soul), hifz al-aql (safeguarding the intellect), hifz an-nasl (safeguarding offspring), and hifz al-mal (safeguarding property), with the most significant impact felt on the aspect of hifz al-mal due to decreased income, which in turn affects the overall quality of life of farmers